(untitled) (Global Journal of Science Frontier Research, 2023)
The current definition of quality is the degree to which a group of intrinsic attributes fulfills the requirements The definition has two major drawbacks it is subjective quality and no positiveness restrictions on the requirements that are met The current definition of quality can be transformed into quality is positive degree by simply replacing the requirements met by intrinsic characteristics with positive objective and abstract general social requirements This new definition of quality can overcome the shortcomings of the original definition of quality It has positiveness objectiveness and abstract and it is very symmetrical and coordinated with the value definition of positive effect